1982
DOI: 10.6028/nbs.ir.82-2485
|View full text |Cite
|
Sign up to set email alerts
|

Symbols for industrial safety

Abstract: Written signs are commonly used in industrial sites to provide hazard warnings and safety information. The use of safety symbols may increase the effectiveness of safety communication, because such signs are language-free, and because they can be recognized more rapidly and accurately than written text even under some conditions of interference and distraction. The effectiveness of safety symbols critically depends upon the selection of symbolic images which are readily understandable to the intended audience.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…One of the most common methods is simply to ask people to write down a brief definition of the meaning of a sign (Brainard et al, 1961;Walker et al, 1965;Cahill, 1975;Easterby and Zwaga, 1976;Collins and Lerner, 1982). In addition to indicating the understandability of the symbol, wrong answers from the definition procedure provide insight into the kinds of confusions and misunderstanding associated with a particular symbol.…”
Section: Methods Of Evaluationmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the most common methods is simply to ask people to write down a brief definition of the meaning of a sign (Brainard et al, 1961;Walker et al, 1965;Cahill, 1975;Easterby and Zwaga, 1976;Collins and Lerner, 1982). In addition to indicating the understandability of the symbol, wrong answers from the definition procedure provide insight into the kinds of confusions and misunderstanding associated with a particular symbol.…”
Section: Methods Of Evaluationmentioning
confidence: 99%
“…Simply selecting a pictorial to convey a safety message from existing catalogues such as Dreyfuss (1972) Collins and Lerner (1982) found that several Internationally proposed life-safety symbols communicated messages that were opposite to their Intended message to a large number of people. Before symbols are selected for mining applications, their effectiveness In communicating the Intended message to members of a mining population must be evaluated.…”
Section: Framework For the Study Of Safety Symbols And Hazard Pictorialsmentioning
confidence: 99%
See 3 more Smart Citations